2018
DOI: 10.1177/0021998318796155
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of water in glass fiber reinforced polymer composites at different temperatures

Abstract: This study examines the effects of temperature and fiber and matrix diffusivities on the diffusion of fluid in glass fiberreinforced polymer composites. Glass fiber-reinforced polymer thin plates were immersed in deionized water at two temperatures: room temperature and 50 C. During the diffusion process, the overall mass changes and dimension changes were recorded, which relate to the volumetric change and the through-the-thickness strain. Different constitutive models are considered in order to understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 37 publications
5
16
0
Order By: Relevance
“…Temperature settings were monitored using an Omega temperature and humidity data logger, controlled using heat lamps and automatic lighting controllers. Muliana et al 35 reported for a similar composite material a water uptake of around 1% at full saturation after 100 days of exposure at 50 C. For the sample dimensions used in the current study (i.e. 5 mm  6 mm  6 mm) and a nominal density of 1860 kg/m 3 , a 1% water uptake corresponds to 3 mg increase in weight based on the aforementioned study.…”
Section: Woven Fiberglass Specimenssupporting
confidence: 50%
“…Temperature settings were monitored using an Omega temperature and humidity data logger, controlled using heat lamps and automatic lighting controllers. Muliana et al 35 reported for a similar composite material a water uptake of around 1% at full saturation after 100 days of exposure at 50 C. For the sample dimensions used in the current study (i.e. 5 mm  6 mm  6 mm) and a nominal density of 1860 kg/m 3 , a 1% water uptake corresponds to 3 mg increase in weight based on the aforementioned study.…”
Section: Woven Fiberglass Specimenssupporting
confidence: 50%
“…The weight was then described as “dried” weight. During the moisture absorption test, the sample weight was recorded for a maximum of 5 days to reach equilibrium: Initially at every 2 h for the first 24 h, and subsequently followed at 4-h intervals for the next 24 h, then at every 6 h for the next 24 h, and every 24 h for the final 48 h. The percent mass change in each specimen is calculated in accordance to Equation (2), where M% is the percent mass change in the samples, M t is the current mass of the combined fluid and solid at time t, and M solid is the mass of solid measured before the test, at ambient conditions [ 46 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Various studies have been performed on swelling of FRPs [10,13,[17][18][19][20][21][22][23][24][25] and, more recently, on hygroscopic swelling in textile composites [26,27]. The works available in the literature have addressed several aspects of hygroscopic swelling in composites, from the nature of swelling in polymeric matrix [3,10,28,29], to the influence of swelling on the fluid diffusion in polymers [13,16,23,30,31], to the development of micromechanical models to predict transverse swelling [17,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Coran et al [21] and Daniels [22] analyzed swelling of reinforced rubbers by means of thermodynamic theory of elasticity, confirming an orthotropic swelling behaviour and relating the elastic constants to the swelling constants of the rubber composite. Fan et al [23] modelled a coupled diffusion and swelling of fiber-reinforced composites. Meng et al [25] developed a multiscale model for coupled moisture diffusion and swelling in FRPs by means of finite element (FE) analysis.…”
Section: Introductionmentioning
confidence: 99%